Climate Change Coverage and the Performance of Green and Brown Equities - Flygare,Anton; Tingets,Fredrik (2023)
Climate change has emerged as one of the world’s most pressing issues, a development that has prompted investors to shift their focus accordingly, catalysing a significant increase in green investments. This study is set against this backdrop, focusing on the performance of portfolios of European firms classified as low or high emission intensity – green or brown respectively – during an eight-year period, from January 2010 to June 2018. Furthermore, we aim to explain the difference in performance using media coverage of climate change. We also conduct a panel data analysis to investigate the difference in individual firms reaction to climate change reporting, emissions intensity and the interaction between these terms. We find a significant discrepancy in the performance of green and brown portfolios, and can show that the green portfolio has a significant positive alpha as well as a positive relationship to an increase in climate change concerns. On a firm-level, we also find that firms with higher emissions intensity outperforms when there’s no news reporting about climate change and that firms with higher emissions intensity react worse than their low counterpart when there’s an increase in climate change news reporting.
Keywords: climate change; green investments; equities; sustainability; news